The complete book 3 collection, disc 1. - 1987-; DeSena, Jack; 1988-; Whitman, Mae; 1993-; Eisen, Zach Tyler; Paramount Pictures Corporation; Nickelodeon (Television network) (Paramount, 2008)
Aang faces new challenges, difficult decisions, and secrets that are revealed. Includes 21 episodes, never- before-seen features, and much more.
The beach.
Rating: PG-13; for sequences of strong violence, some disturbing images and suggestive material
CHV rating: PG.
Keywords: Reincarnation; Martial arts; Magic; Animated television programs; Fantasy television programs; friendship; Drama; Magic; Drama; Drama; Reincarnation; Friendship; Drama; Martial arts; Drama; Action and adventure television programs; Video recordings for the hearing impaired